Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1161/circep.115.002725
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Freezing Time and Balloon Size on the Thermodynamics and Isolation Efficacy During Pulmonary Vein Isolation Using the Second Generation Cryoballoon

Abstract: BackgroundRecently, pulmonary vein isolation (PVI) using the second generation cryoballoon, introduced as a therapy for patients with drug-refractory atrial fibrillation, has shown better outcomes than with the first generation cryoballoon. [1][2][3][4][5] However, some questions about the second generation cryoballoon remain. Several studies in cryobiology have shown that prolongation of freeze duration produces a greater destructive effect in noncardiac tissue. 6,7 However, ablation duration to achieve acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 14 publications
3
33
1
Order By: Relevance
“…The recommended freeze dose was 4 minutes with a bonus application based on the preclinical study data. However, recent clinical and experimental studies have shown that even a short freeze cycle, such as a single 3‐minute freeze technique without bonus applications, is effective in achieving an acute PVI and AF freedom. Therefore, a single 3‐minute freeze hypothetically might be sufficient with this new technology.…”
Section: Discussioncontrasting
confidence: 79%
“…The recommended freeze dose was 4 minutes with a bonus application based on the preclinical study data. However, recent clinical and experimental studies have shown that even a short freeze cycle, such as a single 3‐minute freeze technique without bonus applications, is effective in achieving an acute PVI and AF freedom. Therefore, a single 3‐minute freeze hypothetically might be sufficient with this new technology.…”
Section: Discussioncontrasting
confidence: 79%
“…During 4‐minute ablations, additional mean temperature drop from 3 to 4 minutes is roughly –1/–2 °C. These findings might be explained by previous experimental observations, reporting that cryoablation lesion size measured by ICE grows progressively during the first 3 minutes of freezing in atrial myocardium, and additional 1‐minute ablation duration (from 3 to 4 minutes) does not determine further benefit since adequate and transmural tissue damage is already achieved . Therefore, although optimal ablation duration remains to be defined, a single 3‐minute freeze might be sufficient with this novel technology.…”
Section: Discussionmentioning
confidence: 88%
“…However, the ideal freezing duration and the adequate number of cycles using the novel CB‐Adv remain to be determined. Although current recommendations suggest 4‐minute freeze duration using a bonus application, preclinical experiences showed that a shorter freeze cycle time is highly effective in terms of acute pulmonary vein isolation (PVI) . Moreover, recent clinical studies demonstrated that this novel catheter achieves durable PVI with significantly shorter freeze cycles duration with a promising rate of arrhythmia freedom in the mid‐term clinical follow‐up, questioning the need of an “insurance” freeze when isolation is already achieved .…”
Section: Introductionmentioning
confidence: 99%
“…Similar in vivo experiments have been conducted that measure the cryoballoon freeze characteristics under different study design parameters . Specifically, direct surgical attachment of thermocouples into cardiac and surrounding tissues in canine models have measured time, temperature, and distance relationships during a cryoballoon freeze .…”
Section: Discussionmentioning
confidence: 99%